Postoperative encephalopathy: Pathophysiological and morphological bases of its prevention under general anesthesia - A. M. Ovezov; A. V. Knyazev; M. V. Panteleeva; M. A. Lobov; M. N. Borisova; A. V. Lugovoy (Неврология, нейропсихиатрия, психосоматика, 2015)
In vitro and in vivo studies have provided sufficient evidence of the neurotoxicity of general anesthetics and their ability to cause postoperative cognitive dysfunction (POCD). The latter is one of the undesirable phenomena associated with general anesthesia. Recently, the prevention of postoperative cognitive impairments has been of particular relevance because of their high incidence, longer length of hospital stay, higher cost of treatment, worse quality of life in patients, and no approaches to drug correction and prevention. The review gives data on the negative effects of general anesthesia in patients of different age groups, highlights the pathogenetic mechanisms of POCD, and proposes its possible drug prevention and treatment strategies: identification of patients at high risk for POCD and both pre- and postoperative neuropsychological testing; intraoperative POCD prevention using a package of measures and, if inefficient, drug correction of found cognitive impairments just in the early postoperative period.